On Measuring Multidimensional Deprivation - Pattanaik, Prasanta K.; Xu, Yongsheng (Journal of Economic Literature, 2018)
This essay presents a critical review of the recent book by Alkire et al. entitled Multidimensional Poverty Measurement and Analysis, and, in the course of doing so, it also discusses some general issues that come up in this context. We outline the basic structure of the problem of measuring multidimensional deprivation and critically evaluate the methodology adopted by Alkire et al. (2015). In particular, we discuss some problems associated with the methods used by them to identify the deprived and to aggregate individual deprivations so as to derive an index of social deprivation. We examine the interpretation in terms of unfreedoms of individuals, which Alkire et al. put on one of their measures of social deprivation. We also suggest a variant of their methodology for measuring multidimensional deprivation.( JEL C38, E02, I32, Z13)